Adsorption Equilibrium and Kinetic Studies of Methylene Blue Dye Using Groundnut Shell and Sorghum Husk Biosorbent (Journal of Environmental Bioremediation and Toxicology, 2020)
The Groundnut Shell (GS) and Sorghum Husk (SH) was used as an adsorbent for adsorption of Methylene Blue (MB) dye. The adsorbent was characterized using FTIR and Proximate analysis, Fourier transforms infrared spectroscopy (FTIR) spectrum showed the presence of absorption bands typical of a plant-based biomaterial. The effects of various experimental parameters, such as initial dye concentration, and contact time on the adsorption extent were investigated. The results showed that the percentage removal of MB dye was increased by increasing the concentrations of dye. The dye concentration was determined by spectrophotometry. Langmuir, Freundlich, Temkin and Harkins and Jura models were used to representing the equilibrium data. The Langmuir model was more adequate to represent the equilibrium data for MB with GS, whereas the Temkin model fitted well to both GS and SH for MB. The maximum adsorption capacity was found to be 7.052 mg/g and 15.3846 mg/g for GS and SH, respectively with MB dye. Adsorption data were modelled using the pseudo-first and pseudo-second-order kinetic equations, power function and Elovich models. It was seen that the pseudo-second-order kinetic equation could best describe the sorption kinetics for all the adsorption processes. It was concluded that GS and SH adsorbent can be utilized as an efficient low-cost adsorbent for removal of Methylene Blue dye.
Keywords: Adsorbent; Methylene Blue; Biosorption; Isotherms; Kinetics